2011
DOI: 10.1126/science.1200684
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Role of Agouti in Color Pattern Evolution

Abstract: A regulatory mutation affecting expression of the Agouti gene shows color-specific selection in beach mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(201 citation statements)
references
References 26 publications
8
188
2
3
Order By: Relevance
“…Indeed, this is what we observed for the endocytosis complex adaptations, whose pleiotropic effects on morphology have apparently been compensated by other loci. Another point of contrast is that nearly all previous studies of cis-regulatory adaptation have focused on single genes (with a few exceptions [Fraser 2011]) (Shapiro et al 2004;Colosimo et al 2005;Gompel et al 2005;Miller et al 2007;Prud'homme et al 2007;Wray 2007;Rebeiz et al 2009, Manceau et al 2011. Our results highlight a previously unknown mode of evolution: polygenic cis-regulatory adaptation acting at the level of a physically interacting module.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Indeed, this is what we observed for the endocytosis complex adaptations, whose pleiotropic effects on morphology have apparently been compensated by other loci. Another point of contrast is that nearly all previous studies of cis-regulatory adaptation have focused on single genes (with a few exceptions [Fraser 2011]) (Shapiro et al 2004;Colosimo et al 2005;Gompel et al 2005;Miller et al 2007;Prud'homme et al 2007;Wray 2007;Rebeiz et al 2009, Manceau et al 2011. Our results highlight a previously unknown mode of evolution: polygenic cis-regulatory adaptation acting at the level of a physically interacting module.…”
Section: Discussioncontrasting
confidence: 54%
“…The first identifies single genes whose expression affects an adaptive trait, often via QTL mapping of the trait followed by detailed investigation of candidate genes. This approach has led to several fascinating examples of gene expression adaptations (Shapiro et al 2004;Colosimo et al 2005;Gompel et al 2005;Miller et al 2007;Prud'homme et al 2007;Wray 2007;Rebeiz et al 2009;Manceau et al 2011). However, the amount of effort required-as well as the need for previously characterized candidate genes within each QTL region-has limited its general applicability.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Deer mice display extensive pigment variation matching the color of their environment (Manceau et al 2010). Fine mapping of this variation revealed that not only the Agouti locus is the major driver of pigment variation (Manceau et al 2011) but also this genetic region decomposes itself into multiple noncoding sub-loci, each tightly associated with parts of the total phenotype (Linnen et al 2013). Various regulatory elements are involved in directing the expression of three alternative isoforms into different body regions (Mallarino et al 2016).…”
Section: Cis-regulatory Evolution Drives Regional Specific Color Shiftsmentioning
confidence: 99%
“…This circumvention of pleiotropy by changes in gene regulation, recently dubbed the Stern-Carroll Rule (3), has been borne out in both animals and plants (e.g., refs. [4][5][6][7][8][9][10]. In each case, transcriptional enhancers appear to have been the target of selection.…”
mentioning
confidence: 99%